Profitability of Small-Scale Tomato (Lycopersicon esculentum) Production in Some Selected Areas in Bangladesh - Samshunnahar, Mst.; Khanum, Romaza; Serajul Islam, M (The Agriculturists, 2016)
A study was conducted to analyze the profitability, contribution of factors in yield and socioeconomic status of small-scale tomato (Lycopersicon esculentum) producing farmers in some selected areas in Bangladesh. The study was based on primary data, collected from 60 farmers, selected using a multi-stage random sampling technique. The main factors of production like, seeds, human labour, tillage, fertilizer, irrigation and insecticides were considered to estimate the impacts on tomato production. Data were analyzed statistically and economically and results were mostly presented in tabular form. Amongst 3 farm size groups, small tomato farmers earned highest profit, followed by medium farmers. Gross returns per acre of small, medium and large farms were Tk. 104180, 95000 and 82600 and their corresponding net returns were Tk. 46978, 45356 and 5354, respectively. Moreover, the undiscounted benefit cost ratio of was the highest for medium farmers (1.91), followed by small farmers (1.82), while it was the lowest for large farmers (1.74). The coefficient of determinations (R2) was about 0.694, which indicates that about 69 percent of variations of tomato production are explained by the independent variables. The result showed that human labour followed by tillage of the variables was significantly positive, which implies that various independent inputs uses had effective contribution to increase tomato production. It was therefore, observed that a considerable improvement took place to increase household income of the studied farmers and to improve the economic conditions with the introduction of small-scale commercial tomato production. The elasticity of different inputs was 0.744 which exhibited the decreasing returns to scale and farmers allocated their resources in the rational stage of production (stage-II). However, lack of quality seed was one of the major constraints in cultivation of tobacco. Effective policy and efficient extension services have therefore, to be ensured to increase income and employment opportunities of the tomato drowers. The Agriculturists 2016; 14(1) 73-82